UPAYA Efforts of the Kamsel Unit in the Implementation of Traffic Dikmas for the Prevention of Traffic Accidents in the Jurisdiction of Blitar Police - Dirgahayu, Ria (Advances in Police Science Research Journal, 2024)
The high number of traffic accidents in the jurisdiction of the Blitar Police Station in 2023 means that there is a need for pre-emptive efforts by the Road and Safety Unit in Blitar Police Station to prevent traffic accidents through traffic education. This research aims to analyze the implementation of traffic education by the Road and Safety Unit in Blitar Police Station, the factors that influence its performance and the implementation of police digitalization. The method used in this research is a qualitative method with a type of field research. Data collection techniques use observation, interviews and document study techniques. The data analysis techniques use data reduction techniques, data presentation and drawing conclusions. The results of this research show that the implementation of Traffic Education by the Road and Safety Unit in the Blitar Police Station can be said to be going well, although there are several findings that make it not yet optimal. The factors that influence its performance include the knowledge and abilities of members, clarity in understanding roles and responsibilities, as well as inventory in implementing traffic education. Meanwhile, the implementation of police digitalization takes the form of creating videos or content about traffic.